Action, Freedom, and Education: Refugees and a "New Beginning". Issue 4 (24th November 2020) - d'Agnese, Vasco
Abstract : In the mid‐2000s, large numbers of refugees from North Africa and the Middle East sought to reach Europe to escape persecution, war, and famine. Images of children, women, and men in inhumane conditions attempting to reach the mainland began to circulate worldwide. This phenomenon culminated in 2015 with the worst immigration crisis in Europe since the end of World War II. In this study, Vasco d'Agnese draws on Hannah Arendt's work to demonstrate that refugees, in embarking on their often excruciating journeys, represent the paradigm of acting, natality, and a "new beginning, " features that, for Arendt, characterize the human experience. Starting from this premise, d'Agnese presents two refugee stories and attempts to foreground their intrinsically educational nature with two aims. The first is that engaging with these stories may help transform the traditional view of refugees as vulnerable, suffering, and needy, and instead promote a view that acknowledges refugees' actions, their agency, and that does justice to the strength, determination, and resiliency they demonstrate in taking the actions they do. The second aim is to show how the renewal of natality represented by such stories serves as a foundation for a different engagement with education. If, as Arendt argues, education is first and foremost about preserving natality, the renewal of natality seen in these refugee stories is one of the best educational examples we may find. In refugee stories, the natality of education is, in a profound sense, actualized.